Hydrothermalism Associeted To Ediacarian Volcanism Of Ait Sawn And Tissouktai (Eastern Anti- Atlas, Morocco) - R. Zahour; G. Zahour; Y. Zerhouni; S. Alikouss; Z. Baroudi; H. El Hadi (European Scientific Journal, ESJ, 2016)
In the South East of Ouarzazate (south west of the Saghro massif, Anti Atlas) outcrop the geological formations of Ait Sawn and Tissouktai. These, attributed to the Ediacaran (or terminal Neoproterozoic), consist of basic volcanic facies, intermediate and acid intercalated with pyroclastics and epiclastic levels. This set is traversed locally by acidic veins. The rocks studied suffered intense weathering processes marked by the development of secondary minerals which are also formed in the hydrothermal veins and at the expense of the primary magmatic minerals and mesostasis. The main paragenesis of mineralisation consists of hematite, malachite, chalcocite, pyrite, barite, epidote, quartz, chlorite, calcite, albite, sericite and iron oxides. Paleogeography sector is governed by inherited active faults of the Pan African base. Magmatism studied seems to be guided by these tectonic lineaments during the terminal Proterozoic extension. The reactivation of these tectonic structures, after the Cambrian, and probably during the Variscan and / or Atlasic, is certain. Field investigations, supplemented by microscopic and geochemical study, indicate that much of the mineralization associated with volcanic Southwest Massif Saghro, is related to a hydrothermalisme contemporary with the stage of fault reactivation.